The neural effects of acupuncture for stroke: a protocol for systematic review and meta-analysis based on fMRI - Cai, Shaojie; Zhou, Yihao; Yang, Siyu; Liu, Yichang; Han, Yixiao; Wang, Dongyan; Shi, Shuai (Frontiers in Neuroscience, 2024)
BackgroundStroke is one of the most common causes of death and is the main cause of persistent and acquired disability in adults worldwide. Acupuncture is recommended by the World Health Organization as an alternative and complementary strategy for stroke treatment. However, the mechanism of the neural effects of acupuncture on stroke is still lacking a uniform conclusion. The purpose of this study is to clarify the neural effects of acupuncture for stroke from the perspective of neuroimaging.MethodsSeven databases, including PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, VIP Database, Wan-Fang Data, and Chinese Biomedical Database, will be searched comprehensively according to the search strategy. All of them will be retrieved from the date of database establishment to December 31, 2023. All randomized controlled trials and observational studies will be considered for inclusion. The risk of bias will be assessed by the Cochrane Risk of Bias tool. Functional imaging of the whole brain in the resting functional state will be the primary outcome. A meta-analysis of primary outcome will be performed using Seed-based D Mapping with Permutation of Subject Images software. The data will be synthesized using a random effects model. Meta-analysis of other clinical data will be performed using RevMan 5.3 software. Publication bias will be assessed through funnel plots. Reports will adhere to the Preferred Reporting Items for Systematic Review and Meta-Analysis.ConclusionThis study will aggregate the results of independent studies to provide overall evidence for the neural effects of acupuncture for stroke.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=500306, Identifier CRD42024500306.